Attrition in HIV care following HIV diagnosis: a comparison of the pre‐UTT and UTT eras in South Africa. (18th February 2021) - Onoya, Dorina; Hendrickson, Cheryl; Sineke, Tembeka; Maskew, Mhairi; Long, Lawrence; Bor, Jacob; Fox, Matthew P.
Abstract: Introduction: Policies for Universal Test & Treat (UTT) and same‐day initiation (SDI) of antiretroviral therapy (ART) were instituted in South Africa in September 2016 and 2017 respectively. However, there is limited evidence on whether these changes have improved patient retention after HIV diagnosis. Methods: We enrolled three cohorts of newly diagnosed HIV‐infected adults from two primary health clinics in Johannesburg from April to November 2015 (Pre‐UTT, N = 144), May‐September 2017 (UTT, N = 178) and October‐December 2017 (SDI, N = 88). A baseline survey was administered immediately after HIV diagnosis after which follow‐up using clinical records (paper charts, electronic health records and laboratory data) ensued for 12 months. The primary outcome was patient loss to follow‐up (being >90 days late for the last scheduled appointment) at 12 months post‐HIV diagnosis. We modelled attrition across HIV policy periods with Cox proportional hazard regression. Results: Overall, 410 of 580 screened HIV‐positive patients were enrolled. Overall, attrition at 12 months was 30% lower in the UTT guideline period (38.2%) compared to pre‐UTT (47.2%, aHR 0.7, 95% CI: 0.5 to 1.0). However, the total attrition was similar between the SDI (47.7%) and pre‐UTT cohorts (aHR 1.0, 95% CI: 0.7 to 1.5). Older age at HIV diagnosis (aHR 0.5 for ≥40 vs. 25 to 29 years, 95% CI: 0.3 to 0.8) and being in a non‐marital relationship (aHR 0.5 vs. being single, 95% CI: 0.3 to 0.8) protected against LTFU at 12 months, whereas LTFU rates increased with longer travel time to the diagnosing clinic (aHR 1.8 for ≥30 minutes vs. ≤15 minutes, 95% CI: 1.1 to 3.1). In analyses adjusted for the time‐varying ART initiation status, compared to the pre‐ART period of care, the hazard of on‐ART LTFU was 90% higher among participants diagnosed under the SDI policy compared to pre‐UTT (aHR 1.9, 95% CI: 1.1 to 2.9). Conclusions: Overall, nearly two‐fifths of HIV positive patients are likely to disengage from care by 12 months after HIV diagnosis under the new SDI policy. Furthermore, the increase in on‐ART patient attrition after the introduction of the SDI policy is cause for concern. Further research is needed to determine the best way for rapidly initiating patients on ART and also reducing long‐term attrition from care.